The influence of continuance intention on users’ well-being and intention to recommend online music streaming applications - Stefan Kenichi Soaloon; Putu Wuri Handayani (Cogent Arts & Humanities)
This study aimed to identify the influence of continuance intention on a user’s well-being and intention to recommend music streaming applications. The quantitative data, which were collected from 713 users of such applications, were analyzed using the covariance-based structural equation modelling method. We interviewed 15 music streaming app users to better understand the result of quantitative data. The study found that perceived usefulness, satisfaction, personalization, and habit influenced continuance intention. It also found that users’ continuance intention influenced their intention to recommend, as well as their well-being. The findings from this study provide guidance for music streaming service providers who wish to improve their services in order to increase users’ continuance intention, intention to recommend, and well-being.